A biophysical model to assess the trade‐off between larval recruitment and catch in southern Australia's largest prawn fishery. (March 2016) - Mcleay, Lachlan; Doubell, Mark; Roberts, Shane; Dixon, Cameron; Andreacchio, Lorenzo; James, Charles; Luick, John; Middleton, John
Abstract: Data from stock assessment surveys, published research and climate sensors were linked to model the interaction between fishing, physical‐oceanographic processes and spatial patterns of larval settlement for western king prawn [ Penaeus ( Melicertus ) latisulcatus ]. This information was used to evaluate the trade‐off between larval recruitment and catch during fishing periods that demand high prices but coincide with spawning. Total rates of larval settlement were maximized when tidal currents and atmospheric physical‐forcing components were coupled with simulations of larval swimming behaviour under average gulf temperatures. Average gulf temperatures sustained longer larval durations and increased larval settlement rates by over 12% compared with warmer gulf conditions simulated under a scenario of global warming. Reproductive data coupled with outputs from the biophysical model identified consistent inter‐annual patterns in the areas contributing to larval settlement success. Areas located in the north‐east, and central‐west of the fishery, consistently contributed to over 40% of all larvae reaching a settlement in each year. Harvest sensitivity analyses indicated that changes in the spatial patterns of pre‐Christmas fishing could lead to improvements in overall rates of the larval settlement while maintaining or improving the levels of catch. Future studies to refine the model inputs relating to physical processes, larval behaviour and mortality rates for P. latisulcatus coupled with surveys of juvenile prawn abundance to ground truth the modelled predictions, would allow stock recruitment relationships to be more closely examined and inform adaptive management of the fishery in the future.